Uprość wyrażenia:
a) (x + 1)2 – 2x2
b) -2(3x – 1)2 + 18x2
c) 3(2a + 1)(2a – 1)
d) (x + 8)(x – 8) – (x2 – 8)
e) –(x – 4)2 + (x + 4)2
f) (3t – 1)2 – (3t +1)(3t – 1)
g) ((x+1)^2)/2 + 1/2(2x – 1)2
h) 1/3(x – 6) – ((x-3)(x+3))/3

Zapisz w postaci sumy.

a) 2(2√3 – √5)
b) - √3(1 + 2√3)
c) (√5 + 1)2
d) (5√2 - 1)(5√5 + 1)
e) (2√2 - 1)2
f) (2√3 + 3)(3 - 2√3)
g) (2 + √5)(1 - √3)
h) 2√3(7√3 - 1)2
i) (5√2 - 1)2(2√2 + 1)

trzeba zastosować wzory skróconego mnożenia. ;)
z góry dziękuję ;*

2

Odpowiedzi

2010-04-04T00:01:39+02:00
Uprość wyrażenia:
a) (x + 1)2 – 2x2=x²+2x+1-2x²=-x²+2x+1
b) -2(3x – 1)2 + 18x2=-2(9x²-6x+1)+18x²=-18x²+12x-2+18x²=12x-2
c) 3(2a + 1)(2a – 1)=3(4a²-1)=12a²-3
d) (x + 8)(x – 8) – (x2 – 8)=x²-8-x²+8=0
e) –(x – 4)2 + (x + 4)2=-x²+8x-16+x²+8x+16=16x
f) (3t – 1)2 – (3t +1)(3t – 1)=9t²-6t+1-9t²+1=-6t+2
g) ((x+1)^2)/2 + 1/2(2x – 1)2=1/2x²+x+1/2+1/2*4x²-1/2*4x+1/2*1=
1/2x²+x+1/2+2x²-2x+1/2=2 i 1/2 x²-x+1
h) 1/3(x – 6) – ((x-3)(x+3))/3=1/3x – 2-1/3 x²+3=-1/3 x²+1/3x+1

Zapisz w postaci sumy.

a) 2(2√3 – √5)=4√3 –2 √5
b) - √3(1 + 2√3)= - √3 - 6
c) (√5 + 1)2=5+2√5+1=6+2√5
d) (5√2 - 1)(5√5 + 1)=25√10+5√2-5√5-1
e) (2√2 - 1)2=8-4√2+1=9-4√2
f) (2√3 + 3)(3 - 2√3)=9-12=-3
g) (2 + √5)(1 - √3)=2-2√3+√5-√15
h) 2√3(7√3 - 1)2= 2√3(147 - 14√3+1)=294√3 - 84+2√3
i) (5√2 - 1)2(2√2 + 1)=(50-10√2+1)(2√2 + 1)=10√2+50-40-10√2+2√2+1=
11+2√2
  • Roma
  • Community Manager
2010-04-04T00:09:09+02:00
Uprość wyrażenia:
a)
(x + 1)² – 2x² = x² + 2x + 1 - 2x² = - x² + 2x + 1

b)
-2(3x – 1)² + 18x² = -2(9x² - 6x + 1) + 18x² = -18x² + 12x - 2 + 18x² = 12x - 2

c)
3(2a + 1)(2a – 1) = 3(4a² - 1) = 12a² - 3

d)
(x + 8)(x – 8) – (x² – 8) = x² - 64 - x² + 8 = - 56

e)
–(x – 4)² + (x + 4)² = -(x² - 8x + 16) + x² + 8x + 16 = -x² + 8x - 16 + x² + 8x + 16 = 16x

f)
(3t – 1)² – (3t +1)(3t – 1) = 9t² - 6t + 1 - (9t² - 1) = 9t² - 6t + 1 - 9t² + 1 = -6t + 2

g)
((x+1)²)/2 + ½(2x – 1)² = ½(x² + 2x + 1) + ½(4x² - 4x + 1) = ½x² + x + ½ + 2x² - 2x + ½ = 2½x² - x + 1

h)
⅓(x – 6) – ((x-3)(x+3))/3 = ⅓x - 2 - ⅓(x² - 9) = ⅓x - 2 - ⅓x² - 3 = - ⅓x² + ⅓x - 5

Zapisz w postaci sumy.
a)
2(2√3 – √5) = 4√3 - 2√5 = 4√3 + (-2√5)

b)
- √3(1 + 2√3) = - √3 - 6 = - √3 + (- 6)

c)
(√5 + 1)² = 5 + 2√5 + 1 = 6 + 2√5

d)
(5√2 - 1)(5√5 + 1) = 25√10 + 5√2 - 5√5 - 1 = 25√10 + 5√2 + (-5√5) + (- 1)

e)
(2√2 - 1)² = 8 - 4√2 + 1 = 9 + (- 4√2)

f)
(2√3 + 3)(3 - 2√3) = (3 + 2√3)(3 - 2√3) = 9 - 12 = - 3

g)
(2 + √5)(1 - √3) = 2 - 2√3 + √5 - √15 = 2 + (- 2√3) + √5 + (- √15)

h)
2√3(7√3 - 1)² = 2√3(147 - 14√3 + 1) = 294√3 - 84 + 2√3 = 296√3 + (- 84)

i)
(5√2 - 1)²(2√2 + 1) = (50 - 10√2 + 1)(2√2 + 1) = (51 - 10√2)(2√2 + 1) = 102√2 + 51 - 40 - 10√2 = 92√2 + 11